Numerical analysis in rock engineering - Wang, Zhengguo. (2009)
Rock engineering is the study used when designing any structures built in or on rocks. These structures include building foundations, dams, tunnels, slopes and mines. Adequate knowledge on how rock mass responses to different loadings and the factors that affect the response are of very great importance in most Civil Engineering works.